Συστήματα υποστήριξης ιατρικών αποφάσεων με εφαρμογή στο σακχαρώδη διαβήτη τύπου 2 - Σαΐτη, Κυριακή Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2016)
Why is so important to develop expert systems especially for diabetes mellitus and what are the characteristics of that disease? This disease afflict many people worldwide with rates steadily growing every year affecting the every lives of patients in many areas (e.g. socially , economically etc). This project describes the identity of diabetes mellitus,tested the data from patients and recognizes the effectiveness of the expert systems to confront with the requirements of that disease. Results from the processing of data (6 patients-two females and 4 males,between 27-47 years old) shows how important is to develop a system supporting patients in cooperation with experts to strengthen them take the optimum decisions.There are also some issues that arise from the data mining and the first one is about the quality of data.The need for information is so important as the quality of it in order to be able to make the right decision. . . .